Rekonstruksi Doktrin Wanprestasi dalam Perjanjian Influencer Marketing: Analisis Risiko Algoritma dan Komodifikasi Reputasi Digital - Raul Gindo Cahayo; Nur Octorise Siahaan; Bryan Joseph Putra; Ricky Joeshel March; Luthfi Naufan Zulfikar (Media Hukum Indonesia (MHI), 2026)
The massive transformation of the digital economy has significantly reconstructed the paradigm of global advertising toward the influencer marketing ecosystem. Within this framework, the core of the agreement is no longer confined to mechanical content creation services but has shifted toward the commodification of social capital, cyber reputation, and the achievement of immaterial digital performance metrics. This study aims to reformulate new parameters for identifying breach of contract (wanprestasi) by integrating algorithmic risk variables, while simultaneously designing an adaptive, proportional, and contextual legal dispute resolution model for the digital creative industry in Indonesia. This study employs a normative-empirical legal research method analyzed through a socio-legal approach. The research findings indicate that the classic doctrine of breach of contract under the Indonesian Civil Code (KUHPerdata) experiences a functional gap when confronted with digital disruptions, such as reach degradation caused by shadowbanning and platform algorithmic anomalies. Furthermore, violations of moral clauses that trigger negative public sentiment can be categorized as an implicit failure of performance since it jeopardizes brand safety. From the perspective of procedural law, digital evidence such as screenshots of performance metrics is highly vulnerable to visual manipulation, thus highlighting the urgency of strengthening the "right to audit" clause and verification via digital forensics. Conventional court litigation is deemed unaccommodating due to its protracted nature and its potential to degrade the parties' reputations.